Design and analysis of metallic photonic band gap cavity for a Gyrotron - Ashutosh; Jain, P.K. (My University, 2012)
Design and analysis of a 35 GHz metal photonic band gap (PBG) resonant cavity operating in the TE041-like mode has been presented. The dispersion characteristics of a 2D metal PBG structure comprising of triangular array of rods has been obtained using FDTD method. Global band gap regions have been obtained to be used for the PBG cavity design. A mode map has been also generated to examine the occurrence of the possible modes in the PBG cavity. Electromagnetic simulation of the designed PBG cavity has been performed to study the operating modes and quality factors. Role of the number of metal rods layers around the defect in PBG structure has also been illustrated for confining the desired mode and deciding the diffractive quality factor. PBG cavity results have been compared with the analogous cylindrical cavity for the designed mode along with the possible nearby modes to examine the mode competition. It has been found that the mode competition has been successfully reduced in designed PBG cavity and nearly a single mode operation is achieved. It is hoped that present study would be useful for the application of the metal PBG structures in the Gyrotron devices to alleviate the mode competition problem while operating in the higher order modes.
Keywords: FDTD; Gyrotron; PBG structure